Renal Tubular Dysfunction Linked to Tenofovir in Antiretroviral Therapy in HIV-Infected Patients - Renato Ferneda de Souza; Fernando Gongora Rubio (Baiman Bauntung Batuah Center, 2020)
Introduction: tenofovir disoproxil fumarate (TDF) has low general toxicity and can lead to moderate reduction in glomerular filtration rate (GFR) and a larger prevalence of renal tubular dysfunction (RTD). The mechanism of RTD has been attributed to the mitocondrial lesion in the proximal tubule cells caused by the increase of the intracelular TDF concentration. Aditionaly, host´s genetic polymorphisms have been considered one of the TDF concentration increasing causes. RTD can be characterized by the deficiency in the solutes reabsorption as bicarbonate, uric acid, phosphate, glucose and low weight molecular proteins. Objectives: verify the prevalence of renal tubular dysfunction in the people living with HIV (PLWH) on TDF treatment, identify the risk factors associated and compare the 24-hours urine findings with the serum creatinine and its calculated clearance for the RTD identification. Methods: prospective case control study, performed between january 2011 to december 2015. Results: 163 patients were included in the study, in which 106 (68.4%) didn't use TDF and 57 (31.6%) used TDF. RTD occured in 8 patients that used TDF, a prevalence of 14%. The patients age was identified as significant risk factor for the development of RTD. Proteinuria and the phosphaturia were significant for the diagnosis of RTD. Conclusions: age was determined as risk factor for RTD, mainly in patients over 60 years-old. Phosphaturia and proteinuria showed the greatest diagnosis sensitivity for RTD. The serum creatinine and phosphorus concentration, the creatinine clearance and the stand alone hyperproteinuria should not be used as diagnosis predictors for RTD.